Effect of Exenatide Use on Cognitive and Affective Functioning in Obese Patients With Type 2 Diabetes Mellitus: Exenatide Use Mediates Depressive Scores Through Increased Perceived Stress Levels. Issue 4 (July 2021) - Eren-Yazicioglu, Candan Yasemin; Kara, Buket; Sancak, Seda; Uysal, Sanem Pinar; Yazici, Dilek; Okuroglu, Nalan; Whitton, Alexis E.; Rutherford, Ashleigh V.; Yapici-Eser, Hale
Abstract: Purpose/Background: Glucagon-like peptide-1 (GLP-1) is a molecule used to treat type 2 diabetes mellitus (T2DM). Given their widespread expression in the nervous system, GLP-1 receptors also play a role in regulating mood and cognitive function. Here, we aimed to compare obese patients with T2DM, with or without exenatide (a GLP-1R agonist) use on cognitive and affective functioning. Methods/Procedures: A total of 43 patients with T2DM (23 on exenatide and 20 without exenatide) were evaluated with the Snaith-Hamilton Pleasure Scale, Cognitive Failures Questionnaire, Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7, Childhood Trauma Questionnaire, Perceived Stress Scale (PSS), and Chronic Stress Scale, in addition to laboratory-based measures of reward learning (the probabilistic reward task) and working memory (Letter-N-Back task). Findings/Results: Patients on exenatide had higher body mass index (BMI) (37.88 ± 5.44 vs 35.29 ± 6.30; P = 0.015), PHQ-9 (9.70 ± 4.92 vs 6.70 ± 4.66; P = 0.026), and PSS (29.39 ± 6.70 vs 23.35 ± 7.69; P = 0.015) scores. Other stress scales (Childhood Trauma Questionnaire and Chronic Stress Scale), Generalized Anxiety Disorder-7 scores, response bias, or discriminability as assessed by probabilistic reward task and self-report (Cognitive Failures Questionnaire) and laboratory-based (Letter-N-Back) cognitive measures were not significantly different between groups (both P s > 0.05). Multivariate linear regression analyses adding BMI and PSS as covariates revealed that although BMI had no effect ( P = 0.5), PSS significantly predicted PHQ-9 scores ( P = 0.004). Mediation analysis showed that exenatide users reported higher PSS, with greater PSS associated with higher PHQ-9 levels ( b = 0.236). There was no evidence on exenatide directly influencing PHQ-9 independent of PSS ( c ′ = 1.573; P = 0.305; 95% bootstrap confidence interval, −1.487 to 4.634). Implications/Conclusions: Based on previous research and our findings, exenatide use might be mediating depression scores through disrupting stress responses.